2015
DOI: 10.1007/5584_2015_138
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Lung Function of Small-Volume Conventional Ventilation and High-Frequency Oscillatory Ventilation in a Model of Meconium Aspiration Syndrome

Abstract: For treatment of severe neonatal meconium aspiration syndrome (MAS), lung-protective mechanical ventilation is essential. This study compared short-term effects of small-volume conventional mechanical ventilation and high-frequency oscillatory ventilation on lung function in experimentally-induced MAS. In conventionally-ventilated rabbits, MAS was induced by intratracheal instillation of meconium suspension (4 ml/kg, 25 mg/ml). Then, animals were ventilated conventionally with small-volume (f-50/min; VT-6 ml/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It is associated with various side effects, including injury to the airways and lung parenchyma due to its invasive nature (9). These side effects led to the invention of modern mechanical ventilation methods including high frequency oscillatory ventilation (HFOV), which can be set to trigger or to coincide with the baby's inspiratory efforts (10,11). Recent studies have confirmed the efficacy of modern ventilators as compared to conventional ventilators (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with various side effects, including injury to the airways and lung parenchyma due to its invasive nature (9). These side effects led to the invention of modern mechanical ventilation methods including high frequency oscillatory ventilation (HFOV), which can be set to trigger or to coincide with the baby's inspiratory efforts (10,11). Recent studies have confirmed the efficacy of modern ventilators as compared to conventional ventilators (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…2-4 kg) to those in the neonates. From this reason, utilization of several-weeks-old or adult animals (particularly piglets and rabbits) can be advantageous if various modes of artificial ventilation are performed (Wiswell et al 1994, Renesme et al 2013, Mikusiakova et al 2015 or if treatments are intratracheally delivered (exogenous surfactant, inhaled NO, corticosteroids etc.) (Lam et al 2000, Shekerdemian et al 2004, Mokra et al 2007, Colvero et al 2008, Calkovska et al 2008, Mikolka et al 2013.…”
Section: Model Of Meconium Aspiration Syndrome Induced By Intratrachementioning
confidence: 99%